DYNAMICS OF FOOD ADDITIVE USE IN THE HALAL FOOD INDUSTRY AND APPROACHES FROM AN ISLAMIC PERSPECTIVE - Hakim, Imamul (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstract: This article examines the dynamics of food additive use (BTP) in producing of halal food products and proposes ways to address them from an Islamic perspective. This study uses a narrative review method, which summarizes and analyzes the literature descriptively. This study found that producers frequently commit violations, namely producing food unfit for public consumption by using hazardous food additives as production materials. Therefore, this article offers two main approaches in addition to the regulatory and supervisory approaches carried out by the government: the Halal Supply Chain Management (HSCM) approach in order to maintain the security of the supply chain from upstream to downstream, and a religious approach, where spirituality is the most important element in guiding the determination of business goals. Meanwhile, individual belief in God as the sole supervisor who knows all human activities is an effective means of reducing violations. Keywords: Food Additives; Halal; Food Industry; Islam. Abstrak: Artikel ini bertujuan untuk mengkaji dinamika pengguanaan bahan tambahan pangan (BTP) dalam mewujudkan produk-produk makanan halal dan cara mengatasinya dalam perspektif Islam. Kajian ini menggunakan metode narrative review, yang merangkum dan menganalisis literatur secara deskriptif. Dalam kajian ini mendapati pelanggaran yang sering dilakukan produsen, yaitu memproduksi makanan yang tidak layak dikonsumsi oleh masyarakat melalui penggunaan zat tambahan makanan yang berbahaya digunakan sebagai bahan produksi. Sehingga dalam artikel ini menawarkan dua pendekatan utama selain pendekatan regulasi dan pengawasan yang dilakukan oleh pemerintah, yaitu: pendekatan Halal Supply Chain Management (HSCM) dalam rangka menjaga keamanan rantai pasok dari hulu hingga hilir dan pendekatan keagamaan, dimana spiritualiatas menjadi unsur yang paling penting dalam memberikan panduan untuk menentukan tujuan dalam berbisnis. Sementara itu, keyakinan individu terhadap Tuhan sebagai pengawas tunggal yang mengetahui segala aktifitas manusia adalah sistem pengawasan yang efektif dalam mengurangi pelanggaran. Kata Kunci: Bahan Tambahan Pangan; Halal; Industri Makanan; Islam.